L’émigration corse à Porto Rico au 19e siècle : familles et réseaux familiaux. L’exemple balanin - Marie Jeanne Paoletti Casablanca; Laetizia Castellani (Les Cahiers ALHIM)
The Corsican migration to Puerto Rico is part of the general migration movement from Europe to America during the nineteenth century. Family networks play a central role in these migratory flows. A case study of the Balagne region, located in the northwestern part of the island of Corsica allows us to approach this complex, multifactorial and multi-scalar phenomena : this microanalysis also considers continuities and ruptures that affect “transnational “families”. These migrations can be explained by multiple factors that can be combined (economic, demographic, familial or individual). The Puerto Rican context also contributed to these settlements. From 1815, the Spanish monarchy who wanted to promote the economic development of Puerto Rico made easier the installation of migrants from Spanish friendly nations. The migrant profile is diverse. Family migrations impact the departure chronology as well as the migrant villages role. Family, villages and island flows assumed a protagonist function in the installation of the migrants and their insertion in the Puerto Rican economy and society. The Balanins took part in the development of commercial crops, especially in the western part of Puerto Rico where some of them started cross-cultural families. Part of the migrants remained in Puerto Rico while others returned to their native region.